A Supermodular Game Framework for Power Control of Wireless Sensor Networks. (16th September 2013) - Chen, Zhide; Zeng, Yanqing; Xu, Li
Abstract : We consider a distributed power control scheme for wireless sensor networks. To derive decentralized solutions that do not require complete information and any cooperation among the users, we formulate this problem as a supermodular game, which each user maximizes its utility function provided transmission rate constraints. Through analyzing the supermodular property of the game, the existence and uniqueness of the Nash equilibrium (NE) are established. Furthermore, we propose a distributed price and power update algorithm (DPPA) to compute the solution of the game which is based on myopic best response. Performance evaluations via numerical simulations verify the existence of theNE and the convergence property of the DPPA algorithm.